Harvest season and physiological quality of Enterolobium schomburgkii seeds. Benth. - Mojena, P. A.; Chormiak, D. I. G.; Miranda, Y. (Scientific Electronic Archives, 2016)
The objective of this research was to evaluate the physiological quality of seeds Enterolobium shomburgkii collected in different months of the year 2014. There were made fruit harvests from trees located in the urban area of Sinop-MT, in the months of June, July, August and September. In each crop was rated the number of seeds per fruit, weight of 1,000 seeds, water content of the seeds, dry weight, germination percentage, germination speed index and it was also applied the electrical conductivity test. The results show that the harvest of Enterolobium schomburgkii seeds should be held in August and September.